The master's tools and the master's house: Marxist insights for international law - Tzanakopoulos, A (Oxford University Press, 2024)
Audre Lorde wrote a text in 1979, entitled: ‘The Master’s Tools Will Never Dismantle the Master’s House’. In it, she argued that using the tools of racist patriarchy to examine the fruits of that very same racist patriarchy would only allow the narrowest parameters of change, if any. This is also the predicament faced by any Marxist approach to (international) law. This chapter traces the impact of Marxist thought on international law by focusing on structural aspects of international law: the structure of the (international) legal relation, aka ‘the legal form’; the content of the legal relation with particular emphasis on interpretation; and the justification of the legal relation through ideology. The chapter traces that impact without aspiring to be comprehensive; but aspiring to avoid as much as possible the jargon that tends to alienate (pun intended) non-specialist (in Marxism!) readers, thereby rendering the debate esoteric.